STRATEGI PENGUATAN LITERASI DI INDONESIA: PEMBELAJARAN DARI SISTEM LITERASI JEPANG - Saud, Jefriyanto (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
This study of community services examines the literacy system in Japan and strategies that can be adapted to enhance literacy in Indonesia. The methodology includes literature reviews, observations in schools and libraries, and discussions with literacy communities. The findings indicate that literacy in Japan is supported by an integrated curriculum, educational policies, family involvement, and the utilization of digital technology. Strategies such as ondoku (reading aloud), Bibliobattle, and school-library collaboration have been proven to increase students' reading interest. In Indonesia, major challenges include low reading interest, limited access to reading materials, and a lack of literacy integration within the education system. Therefore, this study recommends implementing school-based literacy strategies, enhancing family engagement, and leveraging digital technology to expand reading access. Collaboration among the government, educational institutions, and literacy communities is expected to sustainably improve literacy in Indonesia.